An economics of paddy during pre-and post-National Food Security Mission in Bhandara District of Maharashtra - Pardhi, Ravishankar; Shrivastava, A. (Annals of Agricultural Research, 2016)
National Food Security Mission (NFSM) was implemented with an objective to increase theproductivity of major cereals and pulses including paddy by providing inputs like seeds, fertilizers,implements, irrigation facility, etc. It resulted in shift in cropping pattern and realization of highernet return. This study was conducted in Bhandara District of Maharashtra to assess the impact ofNFSM on net return of paddy crop. A total of 50 samples including 35 small and 15 medium farmerswere selected from the highest paddy producing block viz. Bhandara block out of seven blocks ofthe Bhandara District. The period of study for pre NFSM and post NFSM was 2006-07 and 2010-11,respectively. The total investment was highest on small farms followed by medium farms in bothpre NFSM and post NFSM period. It was Rs.66834 and Rs.61835 per hectare on small and mediumfarms which was found to be higher as compared to pre NFSM investment of Rs.28255 and Rs.27097per hectare in small and medium farms respectively. The price of paddy in post NFSM was found tobe relatively higher than that of pre NFSM price in the study area. Net income and output-inputratio was higher in post NFSM. Thus, average incremental net income was Rs.9065 per hectarerealizing that paddy cultivation after NFSM was economically viable and profitable over pre NFSMin the study area. Benefit cost ratio of paddy production in post NFSM was found to be higher thanthat of the pre NFSM. The increased B:C ratio clearly indicated the positive impact